BACTERIOLOGICAL INVESTIGATION OF PRAWN CANNERIES I. INCIDENCE OF AEROBIC SPOREFORMERS - NAMBIAR, V NARAYANAN; IYER, K MAHADJEVA (Fishery Technology, 2025)
A detailed bacteriological survey of the prawn <;anneries of Cochin area was carried out to study the nature and type of microorganisms present in the factory environs and their role in causing contaminati9n of the canned products. About 26% of the total of 1030 strains isolated were found to be gram positive spore-formers of the Bacillus type, the cooling water being their major source. Similar types of organisms formed the major group often met with in defective canned prawn samples picked. up from the factories for examinati0n, thus establlishing a correlation between bacterial characteristics and. load. of cooling water and. can contamination.